TLR-2, IL-10 and IL-17-mediated immunity in experimental chemotherapy murine model of systemic candidiasis; cyclophosphamides' impact and roles. (June 2018) - Dehghan, Parvin; Tolouie, Sepideh; Baradaran, Behzad; Nami, Sanam; Morovati, Hamid
Abstract: The majority of immune components such as Toll-like receptor (TLR)-2, interleukin (IL)-17, neutrophils, and IL-10 play pivotal roles in immunity to Candida albicans ( C. albicans ) through identifying and launching inflammatory and regulatory responses. Chemotherapy is one of the most potent risk factors for systemic candidiasis through inducing immunosuppression (mostly cyclophosphamide induced immunosuppression) and there is a sensible lack of study around the immunity to C. albicans in such a situation. In this study, following the establishment of infection and immunosuppression in Balb/c mice model, the mRNA/protein levels of TLR-2, IL-10, IL-17, and Myeloperoxidase (MPO) in serum/kidney were measured using Real-time PCR and ELISA respectively. The survival of mice was checked daily and organ fungal burden was calculated and the histology samples were prepared. Results indicated that the mRNA and protein levels of IL-10, IL-17 and MPO were significantly elevated in immunosuppressed-infected mice ( P  < 0.05). Conversely, the mRNA level of TLR-2 in this mice were significantly decreased ( P  < 0.05). We conclude that, I. cyclophosphamide could induce only a minor state of immunosuppression through depletion of serum neutrophils. II. TLR-2 does not have important roles in developing immune responses in immunosuppressed mice model of systemic candidiasis. Our findings can be applicable for further experimental investigations on patients in clinics for deep understanding of pathogenesis of systemic candidiasis, which could be useful to further broaden our insights for targeted therapy, especially targeting TLR-2 and IL-17, based on siRNA, miRNA or monoclonal antibodies. Graphical abstract: Highlights: Consecutive-high doses of cyclophosphamide severely affects the gene/protein levels of our immune players TLR-2, IL-10, IL-17 and MPO (uninfected-immunosuppressed mice). Cyclophosphamide have no severe effects on the depletion of IL-10, IL-17 levels in mice model of systemic candidiasis. Cyclophosphamide induces the neutropenia and reduces the serum levels of TLR-2 in mice model of systemic candidiasis.